The geology and hydrology of the CarbFix2 site, SW-Iceland - Snæbjörnsdóttir, SÓ; Tómasdóttir, S; Sigfússon, B; Aradóttir, ES; Gunnarsson, G; Niemi, A; Basirat, F; Dessirier, B; Gislason, SR; Oelkers, EH; Franzson, H (2018)
Injection of CO2 and H2S emissions from the Hellisheidi Geothermal Power Plant, SW-Iceland, as part of the CarbFix project, is currently taking place in the Húsmúli reinjection zone. Here we present detailed descriptions of the geology of the reservoir rock in Húsmúli including descriptions of its intrusions, secondary mineralogy and sources of permeability. We further present preliminary results from a modelling study of the Húsmúli reinjection zone that was conducted to obtain better understanding of flow paths in the area. The model was calibrated using results from an extensive tracer test that was carried out in 2013-2015.